Analysis Monetary System Development International, Loan and Investment Foreign and Multinational - Era Mustika; Fildzah Darayanti Mujasmara; Santi Melati; Khairani Matondang; Riza Indrani (International Journal of Asian Business and Management, 2022)
Foreign direct investment in Indonesia is influenced by various factors. The main goal of studies this is for knowing how influence connection growth economy, the international monetary system against foreign direct investment (FDI) and multinational. Data obtained from official internet sites. System changes the other system was caused by the economic turmoil at that time. To this very day the international monetary system is still a concern of all countries and still want change the system Becomes more function optimal. For that writer will discuss related with "System Monetary International". Study this is quantitative research using secondary data indirectly obtained from company, will but data the obtained from site Internet. The population in this study is the international monetary system, loans, investments foreign and multinational. analytical method in this research is analysis data quantitative